Audit Quality in The Consumer Goods Industry Sector - Sitanggang, Tikkos; Fidiasari, Nasyifa; Sitanggang, Juan Moses V. (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to empirically test the effect of audit fees, audit tenure, audit rotation, and auditor reputation on audit quality in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 20192023 period. This study uses secondary data with quantitative methods and purposive sampling techniques, resulting in 63 companies that meet the sample criteria during the 5 years of the study, with a total of 315 observations. The results of this study indicate that audit fees, audit tenure, and auditor reputation have an effect on audit quality, while audit rotation does not affect audit quality.